Predictors of no-reflow in patients with myocardial infarction and ST-segment elevation treated with primary angioplasty. (3rd October 2022) - Cordero, A; Escribano, D; Monteagudo, M; Zuazola, P; Frutos, A; Bertomeu-Gonzalez, V
Abstract: Introduction: The no-reflow phenomenon is a serious complication of coronary intervention, especially in primary angioplasty and effective preventive measures are unknown. Methods: Retrospective study of all patients treated by primary angioplasty in a single center through 4 years. We define no-reflow as the absence of flow immediately after stent angioplasty. The variables associated with this phenomenon were analyzed using binary logistic regression. The delay to primary angioplasty was calculated as the sum of the time to the first medical contact, activation, transfer until arterial puncture. Results: We included 1453 patients, mean age 64.1 years, 21% women, 16.1% Killip >1. The mean delay to primary angioplasty was 180 minutes (interquartile range 125–323). No-reflow was recorded in 81 (5.57%) patients and these patients had a higher mean age (69.37±12.51 vs. 63.76±13.52; p<0.001), higher delay to primary angioplasty (770.93±2056.91 vs. 348.80±749.73; p<0.001), presentation with Killip grade >1 (29.0% 15.36%; p=0.002), in addition to lower systolic blood pressure (121.18±28.63 vs. 113.37±28.22; p=0.021). Regarding coronary angiography, patients who developed no-reflow presented more frequently TIMI-0 (88.89% vs. 70.32%; p<0.001) and a tendency to being the left anterior descending the culprit vessel (46.91% vs. 36.88, p=0.07). In 59.3% of the patients who presented no-reflow, a final TIMI 3 was achieved, with the measurements carried out, compared to (94.9%) of the patients who did not have no-reflow (p<0.001). Multivariate analysis identified the following variables associated with no-reflow: age (OR: 1.03 95% CI 1.01–1.05; p=0.008), delay to primary angioplasty >120 min (OR: 2.70, 95% CI 1.21–6.00; p=0.015), initial TIMI-0 (OR: 3.22, 95% CI 1.57–6.58; p=0.001). In fact, patients aged >40 had a very low incidence of no-reflow (1.72%), regardless of delay to primary angioplasty; however, in patients >70 years of age, the incidence was much higher (figure) Hospital mortality was 9.25% (125 patients) and was almost 4 times higher in patients who presented no-reflow (23.68% vs. 8.39%; p<0.001). Adjusted for age, sex, delay to primary angioplasty diabetes and final TIMI flow, the no-reflow phenomenon was associated with higher hospital mortality (OR: 2.34 95% CI 1.02 4.25; p=0.030) Conclusions: The no-reflow phenomenon has a low incidence but high mortality in patients with ST-segment elevation myocardial infarction treated with primary angioplasty. Age, delay to primary angioplasty and initial TIMI 0 flow are the main predictors of no-reflow. Funding Acknowledgement: Type of funding sources: None.